Juvenile delinquency and gender revisited: the family and power-control theory reconceived - Hadjar, Andreas (European journal of criminology, 2007)
Cross-cultural evidence on the gender gap in delinquency is presented. Based on power-control theory (PCT), gender differences in aggressive behaviour are analysed. We assume that differences in labour force participation between father and mother lead to differences in parental control behaviour towards boys and girls, which in turn lead to different risk-taking preferences and eventually produce gender differences in aggressive behaviour. A revised PCT acknowledges that dominance ideologies also play a role in the genesis of gender differences in delinquency. This proposition is also tested. Analyses are based on data from 319 families (father, mother and two adolescent opposite-sex siblings) from West Berlin, East Berlin and Toronto. The findings support assumptions of PCT but differ substantially between the three cities. Evidence of the link between structural patriarchy and parental style - postulated in the original PCT - is found in East Berlin, whereas the West Berlin and Toronto results fit a modified version of PCT featuring gender-role attitudes (ideological patriarchy).